Dihydroxypentamethoxyflavone down-regulates constitutive and inducible signal transducers and activators of transcription-3 through the induction of tyrosine phosphatase SHP-1 - Kanokkarn Phromnoi (2018)
Because constitutive activation of signal transducers and activators of transcription-3 (STAT3) has been linked with cellular transformation, survival, proliferation, chemoresistance, and angiogenesis of various tumor cells, agents that can suppress STAT3 activation have potential as cancer therapeutics. In the present report, we identified a flavone from the leaves of a Thai plant, Gardenia obtusifolia, 5,3′-dihydroxy-3,6,7,8,4′-pentamethoxyflavone (PMF), that has the ability to inhibit STAT3 activation. PMF inhibited both constitutive and interleukin-6-inducible STAT3 activation in multiple myeloma (MM) cells, as indicated by suppression of STAT3 phosphorylation, nuclear translocation, DNA binding, and STAT3-regulated gene expression. The inhibition of STAT3 by PMF was reversible. We found that the activation of various kinases including Janus-like kinase (JAK)-1, JAK-2, c-Src, extracellular signal-regulated kinases 1 and 2, AKT, and epidermal growth factor receptor, implicated in STAT3 activation, were inhibited by the flavone. It is noteworthy that pervanadate suppressed the ability of PMF to inhibit the phosphorylation of STAT3, suggesting that protein tyrosine phosphatase was involved. PMF induced the expression of SHP-1 and was linked to the dephosphorylation of STAT3, because its deletion by small interfering RNA abolished the PMF-induced constitutive and inducible STAT3 inhibition. STAT3 inhibition led to the suppression of proteins involved in proliferation (cyclin D1 and c-myc), survival (survivin, Mcl-1, Bcl-xL, Bcl-2, and cIAP-2), and angiogenesis (vascular endothelial growth factor). Finally, PMF inhibited proliferation and induced apoptosis of MM cells. PMF also significantly potentiated the apoptotic effects of Velcade and thalidomide in MM cells. Overall, these results suggest that PMF is a novel blocker of STAT3 activation and thus may have potential in suppression of tumor cell proliferation and reversal of chemoresistance in MM cells. Copyright © 2011 The American Society for Pharmacology and Experimental Therapeutics.